The internalization of nationalism and Pancasila for teenager as the value to living in the era of digital transformation - Kusumaningrum, Demeiati Nur; Sulistyaningsih, Tri (Journal of Community Service and Empowerment, 2021)
The COVID-19 pandemic has forced all elements of society to use digital technology in almost all aspects of life. Teenagers are potentially most affected by cybercrime due to the misuse of the internet and other social media networks. The activities to improve students' writing competence by emphasizing the values of nationalism and Pancasila among adolescents reported in this paper aim to support the Indonesian government's digital literacy program and help SMA Aisyiyah Boarding School Malang to publish their school magazine. Internalization of national identity is carried out through the digital literacy program of education by several steps: tutorial, peer-group discussion, review short video, writing competition, demonstration, and technical assistance on publishing management. The results of capacity building consist of 1) improve student writing competency to present as their school magazine contributors, 2) arrange a new editorial team, and 3) publish latest issue of e-magazine through the school's website. Finally, the workshop and technical assistance activities are able to strengthen the awareness of the teenager community toward the era of digital transformation. It has been shown by the result of the quizzes and the student ideas that representing from their essay.